Muscle fiber necroptosis in pathophysiology of idiopathic inflammatory myopathies and its potential as target of novel treatment strategy - Kamiya, Mari; Kimura, Naoki; Umezawa, Natsuka; Hasegawa, Hisanori; Yasuda, Shinsuke (Frontiers in Immunology, 2023)
Idiopathic inflammatory myopathies (IIMs), which are a group of chronic and diverse inflammatory diseases, are primarily characterized by weakness in the proximal muscles that progressively leads to persistent disability. Current treatments of IIMs depend on nonspecific immunosuppressive agents (including glucocorticoids and immunosuppressants). However, these therapies sometimes fail to regulate muscle inflammation, and some patients suffer from infectious diseases and other adverse effects related to the treatment. Furthermore, even after inflammation has subsided, muscle weakness persists in a significant proportion of the patients. Therefore, the elucidation of pathophysiology of IIMs and development of a better therapeutic strategy that not only alleviates muscle inflammation but also improves muscle weakness without increment of opportunistic infection is awaited. Muscle fiber death, which has been formerly postulated as “necrosis”, is a key histological feature of all subtypes of IIMs, however, its detailed mechanisms and contribution to the pathophysiology remained to be elucidated. Recent studies have revealed that muscle fibers of IIMs undergo necroptosis, a newly recognized form of regulated cell death, and promote muscle inflammation and dysfunction through releasing inflammatory mediators such as damage-associated molecular patterns (DAMPs). The research on murine model of polymyositis, a subtype of IIM, revealed that the inhibition of necroptosis or HMGB1, one of major DAMPs released from muscle fibers undergoing necroptosis, ameliorated muscle inflammation and recovered muscle weakness. Furthermore, not only the necroptosis-associated molecules but also PGAM5, a mitochondrial protein, and reactive oxygen species have been shown to be involved in muscle fiber necroptosis, indicating the multiple target candidates for the treatment of IIMs acting through necroptosis regulation. This article overviews the research on muscle injury mechanisms in IIMs focusing on the contribution of necroptosis in their pathophysiology and discusses the potential treatment strategy targeting muscle fiber necroptosis.